2004
DOI: 10.1177/10883576040190040301
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Adults With Asperger Syndrome

Abstract: Six adults With Asperger syndrome (AS) Were intervieWed about their experiences regarding employment. Methods included conducting initial and folloW-up intervieWs, either in person, on the phone, or via e-mail. Repeatedly, difficulties and problems interfering With employment success emerged. All of the adults Who Were intervieWed had difficulty finding Work that Was commensurate With their ability levels and had difficulty maintaining jobs. Recommendations for parents and professionals Working With adults Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
210
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(247 citation statements)
references
References 3 publications
12
210
2
4
Order By: Relevance
“…10 Those who are employed often are employed below their level of education and have difficulty maintaining stable employment. 10,11 Lower cognitive and language functioning have been associated with lower rates of employment. 2,12 Some studies have found that 12% to 24% of youth are not engaged in any productive activities in young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…10 Those who are employed often are employed below their level of education and have difficulty maintaining stable employment. 10,11 Lower cognitive and language functioning have been associated with lower rates of employment. 2,12 Some studies have found that 12% to 24% of youth are not engaged in any productive activities in young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…As a group, they are more likely to be unemployed (without a job), underemployed (in jobs that underutilise their knowledge, skills and experience) and 'malemployed' (in jobs for which they are expressly unsuited) than the population at large (Romoser 2000;Müller et al 2003;Hurlbutt & Chalmers 2004;Robertson 2010;Seltzer et al 2011). Related to this, they demonstrate a comparatively high level of job switching, resulting in fragmented work histories that may limit their potential for ongoing employment and career development, and in turn contribute to stress, depression, isolation, and financial insecurity (Goode, Rutter, & Howlin 1994;Müller et al 2003).…”
mentioning
confidence: 99%
“…However, such studies as have singled out adults with high functioning ASD and presented data specifically related to their employment experiences have tended to show poor outcomes for this group. These include low rates of independent employment; jobs that are not commensurate with the individual's ability levels; and difficulty maintaining jobs (Howlin, Mawhood, & Rutter 2000;Romoser 2000;Howlin et al 2004;Hurlbutt & Chalmers 2004;Cederlund et al 2008;Stuart-Hamilton et al 2009;. In addition, it appears that many adults with high functioning ASD are not receiving the supports at work that they need in order to perform their jobs well (Beardon & Edmonds 2007).…”
mentioning
confidence: 99%
“…setting and maintaining a positive relationship with supervisors. In a qualitative study by Hurlbutt et al [26], adults, with ASD reported experiencing more challenges with navigating the social expectations of the workplace than with the work-tasks themselves. Limitations on employment, social relationships, and adaptive behavior place adults with ASD at high risk for isolation and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%